Social support, educational, and behavioral modification interventions for improving household disaster preparedness in the general community-dwelling population: a systematic review and meta-analysis - Amberson, Taryn; Heagele, Tara; Wyte-Lake, Tamar; Couig, Mary Pat; Bell, Sue Anne; Mammen, Manoj J; Wells, Valerie; Castner, Jessica (Frontiers in Public Health, 2024)
Background The efficacy of household emergency preparedness interventions for community-dwelling, non-institutionalized people is largely unknown. Objective To ascertain the state of the science on social support, educational, and behavioral modification interventions to improve all-hazard household disaster preparedness. Design Systematic review and meta-analysis. Methods Databases, trial registers, reports, and websites were searched, and citation trails followed utilizing replicable methods. Individual, cluster, and cross-over randomized controlled trials of non-institutionalized, community-dwelling populations and non-randomized controlled trials, controlled before-after, and program evaluation studies were included. At least two review authors independently screened each potentially relevant study for inclusion, extracted data, and assessed the risk of bias. Risk of bias was assessed using Cochrane’s RoB2 tool for randomized studies and ROBINS-I tool for nonrandomized studies. Meta-analyses were applied using a random-effects model. Where meta-analysis was not indicated, results were synthesized using summary statistics of intervention effect estimates and vote counting based on effect direction. The evidence was rated using GRADE. Results 17 studies were included with substantial methodological and clinical diversity. No intervention effect was observed for preparedness supplies (OR = 6.12, 95% 0.13 to 284.37) or knowledge (SMD = 0.96, 95% CI −0.15 to 2.08) outcomes. A small positive effect (SMD = 0.53, 95% CI 0.16 to 0.91) was observed for preparedness behaviors, with very low certainty of evidence. No studies reported adverse effects from the interventions. Conclusion Research designs elucidating the efficacy of practical yet complex and multi- faceted social support, educational, and behavioral modification interventions present substantial methodological challenges where rigorous study design elements may not match the contextual public health priority needs and resources where interventions were delivered. While the overall strength of the evidence was evaluated as low to very low, we acknowledge the valuable and informative work of the included studies. The research represents the seminal work in this field and provides an important foundation for the state of the science of household emergency preparedness intervention effectiveness and efficacy. The findings are relevant to disaster preparedness practice and research, and we encourage researchers to continue this line of research, using these studies and this review to inform ongoing improvements in study designs.